The Effect of Duolingo Application Towards Students’ Vocabulary Mastery at the Seventh Grade Students of SMP Negeri 3 Belitang Mulya - Diah Ayu Kurniawati; Eka Agustina; Hastuti Retno Kuspiyah (Channing : Journal of English Language Education and Literature, 2021)
The goal of this study was to determine if there was a significant difference in vocabulary mastery between seventh-grade students at SMP Negeri 3 Belitang Mulya who were taught using the Duolingo program and those who were taught using the conventional approach. Quantitative research, an experimental technique, and a quasi-experimental design were employed. In the academic year2021/2022, seventh graders from SMP Negeri 3 Belitang Mulya were the population. The sample was collected by purposeful sampling, and it consisted of an experimental group of 27 students and a control group of 28 students. The data were collected using a multiple-choice exam and analyzed using the independent t-test in SPSS 22. This investigation found a significant distinction between the experimental and control groups. This meant that students in the seventh grade at SMP Negeri 3 Belitang Mulya may use the Duolingo App to teach and acquire vocabulary.